Risk factors associated with myopia in schoolchildren in Ireland. Issue 12 (11th February 2019) - Harrington, Siofra Christine; Stack, Jim; O'Dwyer, Veronica
Abstract : Aim: To examine the demographic and social factors associated with myopia in schoolchildren in Ireland. Methods: Thirty-seven schools participated, representing a mix of urban and rural schools and schools in socioeconomically disadvantaged and non-disadvantaged areas in Ireland. Examination included cyclopleged autorefraction (1% cyclopentolate hydrochloride). Height and weight of participants were measured. Parents filled in a participant's lifestyle questionnaire, including questions on daily screen time use and daylight exposure. Myopia was defined as spherical equivalent ≤−0.50 D. Results: Data from 1626 participants (881 boys, 745 girls) in two age groups, 6–7 years (728) and 12–13 years (898), were examined. Myopia prevalence was significantly higher in children aged 12–13 years old (OR=7.7, 95%CI 5.1 to 11.6, p<0.001) and significantly associated with non-white ethnicity (OR=3.7, 95% CI 2.5 to 5.3, p<0.001). Controlling for age group and ethnicity, myopia prevalence was also significantly linked with height (p<0.001) and higher in participants in the following groups: using screens >3 hours per day (OR=3.7, 95% CI 2.1 to 6.3, p<0.001), obesity (OR=2.7, 95% CI 1.9 to 3.9, p<0.001), sedentary lifestyle (OR=2.9, 95% CI 1.9 to 4.4, p<0.001), frequently reading/writing (OR=2.2, 95% CI 1.4 to 3.5, p=0.001), less daylight exposure during summer time (OR=5.00, 95% CI 2.4 to 10.3, p<0.001), spring season births (OR=1.9, 95% CI 1.1 to 3.3, p=0.02), paternal history of myopia (OR=2.4, 95% CI 1.8 to 3.3, p<0.001) and bottle fed for the first three months of life (OR=1.7, 95% CI 1.3 to 2.5, p=0.02). Conclusions: The associations found between myopia prevalence in schoolchildren in Ireland and demographic and lifestyle factors suggest that longitudinal research investigating the associations between myopia prevalence and these factors may be beneficial in advising preventative public health programmes.